Correlations between healthcare provider interactions and mental health among transgender and nonbinary adults - Shanna K. Kattari; Matthew Bakko; Hillary K. Hecht; Leonardo Kattari (Elsevier, 2020)
Transgender and nonbinary patients have a wide array of experiences when attempting to access healthcare, including discrimination and having to educate providers about trans people. This study examines the mental health factors connected to transgender and nonbinary patients' experience with providers to determine the likelihood of transgender or nonbinary patients receiving respectful care after a provider knows about the patient's gender identity, and patients' experience of having to educate providers about trans people, controlling for sociodemographic factor. Using data from the 2015 United States Trans Survey (N = 27,715), chi-square tests of independence and multivariate logistic regressions were used to explore the odds of transgender or nonbinary individuals having a positive experience with a doctor or healthcare provider. Of the respondents, 24.31% experienced having to educate a provider about trans people when seeking care, and 62.90% experienced a provider knowing they were transgender or nonbinary and treating them with respect. Those experiencing depression and suicidal thoughts were significantly less likely to have had a provider treat them with respect, and significantly more likely to need to educate their providers. Gender, age, disability status, and educational level were significant across both variables; income was significant regarding having to educate a provider. Healthcare providers need ongoing training and education to improve their care of transgender and nonbinary patients, specifically around acknowledging the multiple backgrounds and experiences of such patients, including those related to mental health, gender, race, age, income, educational level, and disability.